Influence of variety, concentration, and temperature on the steady shear flow behavior and thixotropy of canary seed (Phalaris canariensis) starch gels. (29th March 2016) - Irani, Mahdi; Razavi, Seyed M. A.; Abdel‐Aal, El‐Sayed M.; Taghizadeh, Masoud
Abstract : In this study, the rheological properties of starch gels from two varieties of canary seeds (CDC Maria and CO5041) were investigated. The experimental conditions were different concentrations (4, 6, and 8% w/w at constant temperature of 25°C) and temperatures (25, 40, 55, and 70°C at constant concentration of 6%). All samples showed shear‐thinning and thixotropy behavior at studied conditions. The power‐law model ( R 2  = 0.940–0.987; RMSE = 1.297–15.325) and Casson models ( R 2  = 0.861–0.975; RMSE = 0.211–0.917) were selected to describe time‐independent behavior of the samples. In addition, the first‐order stress‐decay model ( R 2  = 0.89–0.98 and RMSE = 2.84–20.79) described the time‐dependent behavior of canary seed starch samples in the study well. The CO5041 starch gel had higher pseudoplasticity at different concentrations than CDC Maria. Both starches exhibited the same shear‐thinning behavior with increasing temperature. With increasing concentration, the canary seed starch samples showed more shear‐sensitive thixotropic nature and faster rupture rate. The CO5041 starch gel exhibited higher extent of thixotropy than CDC Maria starch gel at different concentrations.